Proposed Design of Performance Management System in Automotive Part Manufacturing Industry: A Knowledge-Based Approach (Case Study PT MM) - Laksamana Naufal Hibban; Gatot Yudoko (Publikasi Indonesia, 2025)
The automotive manufacturing industry in Indonesia plays an important role in driving national industrial growth, with vehicle production exceeding one million units annually and the automotive industry itself contributing 7.63% to GDP and employing around 1.5 million people. PT Mawar Manufaktur (PT MM), as a manufacturer and supplier of automotive components, plays a significant role within this ecosystem. However, amid the intensifying competition in the automotive industry, PT MM faces challenges in enhancing its competitiveness. The current performance management system remains fragmented and primarily focuses on financial and core operational aspects. This study proposes a redesigned Performance Management System (PMS) using the Knowledge-Based Performance Management System (KBPMS) framework. This performance management system combines strategic alignment, interdepartmental integration, and the inclusion of key performance indicators (KPIs) consisting of financial and non-financial indicators. The new PMS is expected to enhance the company's flexibility and competitiveness. The research methodology includes a combination of qualitative and quantitative techniques, such as interviews, literature reviews, external and internal analyses, and the application of the Analytic Hierarchy Process (AHP). The outcome of this study is a comprehensive PMS tailored to the strategic needs and operational context of PT MM. This enables the company to adapt to industry developments, particularly the growing relevance of electric vehicles (EVs), and to sustain long-term growth.